2002
DOI: 10.1161/01.hyp.0000023182.68420.eb
|View full text |Cite
|
Sign up to set email alerts
|

Excess ldosterone Is Associated With Alterations of Myocardial Texture in Primary Aldosteronism

Abstract: Abstract-Hyperaldosteronism has been causally linked to myocardial interstitial fibrosis experimentally, but it remains unclear if this link also applies to humans. Thus, we investigated the effects of excess aldosterone due to primary aldosteronism (PA) on collagen deposition in the heart. We used echocardiography to estimate left ventricular (LV) wall thickness and dimensions and for videodensitometric analysis of myocardial texture in 17 consecutive patients with PA and 10 patients with primary (essential) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
2
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(158 citation statements)
references
References 36 publications
8
140
2
8
Order By: Relevance
“…In particular, the ROC curve analysis showed that the best predictor of hypertension recovery after surgery is the duration of hypertension equal to or shorter than 6 years, in accordance with a recent study by Zarnegar et al (18). In this regard, we can hypothesize that aldosterone excess for long time could induce detrimental and irreversible effects on the cardiovascular system, such as cardiac fibrosis, left ventricular hypertrophy (29)(30)(31) or vascular remodeling with increased intima-media thickness (24), responsible for hypertension persistence in spite of aldosterone normalization after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the ROC curve analysis showed that the best predictor of hypertension recovery after surgery is the duration of hypertension equal to or shorter than 6 years, in accordance with a recent study by Zarnegar et al (18). In this regard, we can hypothesize that aldosterone excess for long time could induce detrimental and irreversible effects on the cardiovascular system, such as cardiac fibrosis, left ventricular hypertrophy (29)(30)(31) or vascular remodeling with increased intima-media thickness (24), responsible for hypertension persistence in spite of aldosterone normalization after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was recently reported that 15 of 23 (65.2%) Japanese patients with APA possessed two somatic mutations in the KCNJ5 gene 5) , suggesting that mutations of the KCNJ5 gene are closely related to the pathogenesis of APA in Japanese patients 5) . It is well known that aldosterone plays a crucial role on the onset of cardiovascular complications, such as myocardial fibrosis and proteinuria [6][7][8][9][10] . The prognostic impact of the abovementioned cardiovascular complications in APA patients is reported to be significantly improved by unilateral adrenalectomy 6,[9][10][11][12] .…”
Section: Evaluation Of Cardiovascular Complications Before and After mentioning
confidence: 99%
“…In particular, a study by Brilla et al demonstrated that an aldosterone infusion with a high salt intake induces both cardiac hypertrophy and myocardial interstitial fibrosis (10). In clinical studies, Rossi et al reported that PA patients exhibit significant changes in the myocardial tissue as compared to essential hypertensive patients, and, secondary to cardiac fibrosis, can serve as an important determinant of myocardial remodeling and impaired tissue stiffness (11). Moreover, in a retrospective study, a twelve-fold increase in the relative risk of atrial flutter or fibrillation was seen in PA patients, as compared to essential hypertensive patients (12).…”
Section: Discussionmentioning
confidence: 99%